SYSTEMATISATION OF FACTORS OF SOCIAL RESPONSIBILITY FORMATION - YERMAKOV, Maksym (Herald of Khmelnytskyi National University. Economic sciences, 2025)
In modern society, social responsibility plays a key role not only for individuals but also for collective entities such as organizations, local communities, and state institutions. The growing complexity of social challenges, the intensification of globalization processes, and the increasing influence of mass media and digital technologies contribute to the emergence of new expectations for responsible behavior. These changes demand a higher level of awareness and accountability in interactions between people, institutions, and society at large. This situation calls for a deeper analysis of the factors that shape social responsibility, with particular attention to their classification, origin, and impact. One of the central objectives in this area is the systematization of influencing factors in order to build a structured and comprehensive understanding of how social responsibility is formed and maintained. However, there is currently a lack of unified and widely accepted approaches to this classification, which reduces the efficiency of practical actions and policies designed to foster responsible behavior in various sectors of society. Therefore, it is essential to examine not only the external but also the internal drivers of socially responsible conduct. This includes psychological, cultural, institutional, educational, and economic factors that interact in complex ways and influence both individual and collective decision-making. A detailed exploration of these elements and their relationships can help build effective strategies for promoting ethical practices, civic engagement, sustainable development, and long-term social stability. Ultimately, enhancing our knowledge of social responsibility factors is key to building a more inclusive, resilient, and ethically grounded society that is better prepared to meet future challenges.